The Impact of Liquidity, Leverage, and Profitability Ratios on Financial Distress - Gami, Emelia Rahmadany Putri; Pakpahan, Dewi Rafiah; Hou, Amin; Hecimovic, Angela (Quantitative Economics and Management Studies, 2025)
This study examines the influence of liquidity, leverage, and profitability on financial distress at PT. Jamu Nyonya Meneer, a traditional herbal medicine company in Indonesia. Using a quantitative descriptive research approach, the study analyzes secondary data from the company's financial statements through multiple regression analysis, hypothesis testing, and correlation analysis. The research focuses on three key financial ratios: Current Ratio for liquidity measurement, Debt to Equity Ratio (DER) for leverage assessment, and Return on Assets (ROA) for profitability evaluation. The findings reveal that liquidity, leverage, and profitability have significant positive effects on financial distress, with the regression equation Y = 23.491 + 0.457X₁ + 0.482X₂ + 0.372X₃. The F-test results (Sig. = 0.02 < 0.05) confirm that all independent variables jointly influence financial distress, while individual t-test results show significant partial effects for Liquidity (Sig. = 0.000), Leverage (Sig. = 0.001), and Profitability (Sig. = 0.000). The coefficient of determination (R²) indicates that 61.5% of financial distress variation is explained by these three variables, while 38.5% is influenced by other factors. Contrary to conventional expectations, higher liquidity and profitability increase financial distress risk, suggesting complex operational dynamics in the herbal medicine industry. The study contributes to financial distress prediction literature and provides practical insights for herbal medicine companies' financial management strategies.